Characterization of liquid state sulfur polymer/epoxy blend as asphalt pavement materials - Kwon, Hyuk; Lee, Albert S.; Lee, Jin Hong; Park, No Kyung; Kim, Goo Dae; Cho, Bongsuk; Cho, Sung-Churl; Yu, Seunggun (한국공업화학회, 2017)
In this study, a liquid state sulfur polymer (LSP) was employed as asphalt pavement materials. The LSP/epoxy asphalt (LSPA) was easily fabricated by mixing LSP and epoxy resin at room temperature. The workability of as-mixed LSP/epoxy mixture was explored by controlling the ratio of epoxy. The asphalt mixture with the epoxy content below 50 wt% exhibited reliable flowability above approximately 12.5 cm. The solidification of LSP was successfully accompanied by simultaneous curing of epoxy. For practical application of pavement on road, the Marshall stability, indirect tensile strength and wheel tracking test were performed. The Marshall stability and indirect tensile strength of the LSPA exhibited an approximate 2-fold increase compared to neat asphalt. Moreover, exceptional durability of the LSPA was achieved through the controllable crushed depth of the pavement under wheel passes of 25,000 cycles. For practical repairing test on the road, the LSPA was cast on a pothole prepared on asphalt road. Our as cast asphalt materials were suitable to heal potholes with seamless interface and the hardening was accomplished within a very short time of 1 h. The hardened LSPA exhibited excellent adhesion strength of approximately 1.95 MPa, enabling the elimination of gaps arising from traffic cycles and climate variation. (C) 2017 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.